A Moodle extension to book online labs - José M. Ferreira (2005)
The social constructivist philosophy of Moodle makes it an excellent choice to deliver e-learning contents that require collaborative activities, such as those that are associated with online labs. In the case of online labs that enable web access to real devices (remote workbenches), access time should be reserved beforehand. A booking tool will avoid access conflicts and at the same time will help the students to organise their time and activities. This paper presents a Moodle extension that was developed within the Leonardo da Vinci MARVEL project, with the objective of meeting this requirement. The booking tool presented enables resource sharing in general and may be used to organise access to any type of scarce resources, such as to online labs and to the videoconferencing rooms that are needed to support collaborative activities.